After mass crime: rebuilding states and communities - Pouligny, Béatrice (United Nations University Press, 2007)
Introduction: Picking up the pieces / Béatrice Pouligny, Simon Chesterman and Albrecht Schnabel -- Methodological and ethical problems : a trans-disciplinary approach / Béatrice Pouligny, Bernard Doray and Jean-Clément Martin -- Contested memories : peace-building and community rehabilitation after violence and mass crimes : a medico-anthropological approach / Roberto Beneduce -- The uses and abuses of culture : cultural competence in post-mass-crime peace-building in Cambodia / Maurice Eisenbruch -- Intimate enemies : reconciling the present in post-war communities in Ayacucho, Peru / Kimberly Theidon -- Origins and aftermaths : the dynamics of genocide in Rwanda and their post-genocide implications / Scott Straus -- You can't run away : former combat soldiers and the role of social perception in coping with war experience in the Balkans / Natalija Baic -- Mass murder, the politics of memory, and post-genocide reconstruction : the cases of Rwanda and Burundi / René Lemarchand and Maurice Niwese -- Speaking from the shadows : memory and mass violence in Bali / Leslie Dwyer and Degung Santikarma -- Shaping political identity through historical discourse : the memory of Soviet mass crimes / Thomas Sherlock -- External contributions to post-mass-crime rehabilitation / Louis Kriesberg -- Re-imagining peace after mass crime : a dialogical exchange between insider and outsider knowledge / Roberta Culbertson and Béatrice Pouligny